Hubungan Tempat Tinggal Remaja Dengan Perilaku Seksual Pranikah di Dusun Air Buaya Kecamatan Kairatu Kabupaten Seram Bagian Barat Tahun 2019 - Maritje Seflin J Malisngorar (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2020)
Premarital sex behavior is a social phenomenon that is very common in society. This is indicated by the high number of sexually transmitted diseases in adolescents such as HIV / AIDS, as a result of poor promiscuity among adolescents such as premarital sexual behavior, so this sexually transmitted disease is more prevalent in adolescence. Then adolescents are never aware that engaging in premarital sexual behavior will harm themselves, such as pregnancy outside of marriage, abortion, destroying morals, tarnishing the good name of the family. Teenagers think that premarital sexual behavior is commonplace for adults and should be followed and imitated by teenagers. To analyze the relationship between adolescent residences and premarital sexual behavior in Dusun Air Buaya, Kairatu Subdistrict, West Seram Regency in 2019. This study used a descriptive analytical research with a cross sectional design, with sample size of 62 respondents, the sampling technique used purposive sampling. In this study the researcher used the Chi-square test with the obtained results of statistical analysis using the Chi-Square test obtained a p-value of 0.022 when compared with the degree of significance (p-value